(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
When we speak of the modern plays, we find that theresponse of the writers to their own time has also moulded their approach, notonly in theme, but also in objective presentation. Dramatic language, asemployed in all Absurdistic plays has undergone a definite qualitative seachange. In a conventional drama language too is conventionally comfortable andis never at cross purpose to the action. The Absurdists, on the other hand,recognize the centrality of language in an unconventional way. In fact,language has been devalued by these writers perhaps because they feel that ithides more things than it reveals. Language, therefore, is used as a.convenient Camouflage to get behind. The audience plays a guessing-game asregards what is being either implied or suppressed. The dramatists areinterested with a new sense in probing the reality lying behind the expressedlanguage. At the advanced period of Twentieth century men and women are passingthrough an age of rapid transition, when the very expressive machinery, of ourthought and emotions, is being dismantled. The dramatists are contributingtheir mite in this ritual of debunking the language, besides putting in agesture of positivistic communication. Language alone is no more considered tobe effectively sufficient for the purpose of precise communication. By severalmaneuvers the Absurdist dramatists satirize the debased quality of cliches andthe Vacuity of smooth, oily conversation.